The Different Sources of Intergenerational Income Mobility in High and Low Income Families - Anders Hjorth-Trolle; Rasmus Landersø (Institute of Labor Economics (IZA), 2024)
This paper studies intergenerational income mobility using register data for 630,000 Danish children and their parents. We document substantial mobility differences across parents' income levels. Decomposing the mobility estimates shows that for children from low income families, intergenerational income persistence is exclusively explained by parents' influence on children's employment. As parents' income increases, education becomes an increasingly dominant factor, except among children from the top-5% where intergenerational income persistence is driven by capital income likely through bequests and business contacts. Finally, we find that progressive public transfers such as those in Denmark suppress the importance of intergenerational transmission of employment.
Keywords: I24; I30; J62; 330; income mobility; education; employment; public transfers